Tantangan utama preservasi naskah kuno berbasis digitisasi - Testiani Makmur; Dudung Abdurahman; Sri Rohyanti Zulaikha; Dafrizal Samsudin (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This research aims to determine the main challenges in preserving ancient manuscripts based on digitization. Research methods. This study used descriptive qualitative method. Data was obtained through literature studies based on scientific works published from 2013 to 2023. A total of 76 scientific works consisting of theses, national and international journals were obtained from the Google Scholar database with the keywords Naskah Kuno”, “Pelestarian Naskah Kuno”, “digitisasi naskah kuno.” Meanwhile in English it is like "Ancient Manuscripts, Preservation of Ancient Manuscripts, and digitization of ancient manuscripts. Results and Discussion. Digitized preservation of ancient manuscripts requires careful budget planning and there must be a third party willing to sponsor it on an ongoing basis. Human resources working in the field of ancient manuscript preservation must understand the factors that cause damage to ancient manuscripts; not phobic of technology; awareness to learn about the use of technology; and ready to improve technology skills. The results of digitizing ancient manuscripts are guaranteed to be accessible in their entirety as mandated by law. Avoiding technological obsolescence requires paying attention to the age of the media so that there is a guarantee of long-term use. Conclusion. This study shows five main challenges in the process of digitizing ancient manuscript preservation, including aspects of budget, policy, human resources, accessibility and technological obsolescence. In the future, preserving ancient manuscripts through digitization must focus on these five aspects, because they are interrelated.